The Effect of Wrist Flexibility and Arm Muscle Strength On The Accuracy of Backhand Backspin Service At The Pingpong Community Club of Bulukumba Regency - Manoppo, Nursartika Putri; Ramli, Ramli; Hakim, Hikmad; Hudain, Muh. Adnan; Bismar, Ahmad Rum (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine whether or not there is an influence of Wrist Flexibility, Arm Muscle Strength and Hand-Eye Coordination on the Accuracy of Backhand Backspin Service of Pingpong Community Club, Bulukumba Regency: The population in this study were athletes of Pingpong Community Club, Bulukumba Regency with a sample of 5 athletes using a purposive sampling technique. The research instruments used were descriptive analysis, data normality test, linearity test, hypothesis test and model suitability test with the help of SPSS version 21.00. The results of the study showed that; (1) There is a direct influence of wrist flexibility on hand eye coordination of athletes of Pingpong Community Club, Bulukumba Regency by 121.1%; (2) The direct influence of arm muscle strength on hand eye coordination of athletes of Pingpong Community Club, Bulukumba Regency by 73.2%; (3) There is a direct influence of wrist flexibility on the accuracy of backhand backspin service of athletes of Pingpong Community Club, Bulukumba Regency by 322.7%; (4) There is a direct influence of arm muscle strength on the accuracy of backhand backspin service strokes of athletes from the Bulukumba Regency pingpong community club by 158.2%; (5) There is a direct influence of hand-eye coordination on the accuracy of backhand backspin service strokes of athletes from the Bulukumba Regency pingpong community club by 3727.8%; (6) There is an influence of wrist flexibility through hand-eye coordination on the accuracy of backhand backspin service strokes of athletes from the Bulukumba Regency pingpong community club by 0.005%; (7) There is an influence of arm muscle strength through hand-eye coordination on the accuracy of backhand backspin service strokes of athletes from the Bulukumba Regency pingpong community club by 121.8%.